IMPLEMENTASI RUANG KOLABORASI PADA DESAIN PUSAT SENI PERTUNJUKAN, Studi Kasus: Pusat Seni Pertunjukan di Kawasan Sriwedari, Surakarta - Ghozali, Ahmad; Ekomadyo, Agus Suharjono (Jurnal Arsitektur Komposisi, 2020)
Surakarta is known as a cultural city that has cultural diversity that must be developed and preserved based on the human resources that are fostered in the arts community. The design of the Performing Arts Center in the Sriwedari area is intended to provide a means of creation, interaction and collaboration between art communities in Surakarta. This paper is structured as a narrative about architectural design that has been carried out, starting with a literature review,formulating design strategies, and implementing them in architectural design. There are several concepts offered, which are 1) the application of traditional Javanese architecture in the use of building geometry and zoning arrangements based on zoning in the Joglo house, 2) the creation of interaction spaces between artists with spatial planning, circulation, and also buildings. envelopes,3) designing spaces with semi-open concepts, open layout and being able to give the openness impression, 4) circulation systems with the concept of free circulation, and 5) building envelopes with semi-open concepts without clearly dividing between inside and outside spaces. Through design, traditional Javanese architecture can be revived to answer the needs of an artist's interaction and collaboration space.